2021
DOI: 10.1186/s13256-021-02855-w
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of vitrectomy for retinal detachment in a patient with Ehlers–Danlos syndrome type IV: a case report

Abstract: Background The Ehlers–Danlos syndrome (EDS) is a group of connective tissue disorders characterized by fragile blood vessels and an increased tendency for bleeding and scarring. Here, we report the outcome of a pars plana vitrectomy for the treatment of rhegmatogenous retinal detachment in a patient with EDS type IV (vascular type). Case presentation A 40-year-old Slovenian man with high myopia, unilateral bullous retinal detachment, and vitreous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…With various reported developments of intraoperative complications such as choroidal detachment, hemorrhage, and subsequent scarring, success of surgical repair for rhegmatogenous retinal detachments in patients with vEDS is especially low ( 35 ). In one case of a patient with type IV EDS presenting with retinal detachment accompanied by vitreous hemorrhage and ten retinal breaks, Lumi et al reported successful repair utilizing a small-gauge vitrectomy with gas tamponade and laser photocoagulation to avoid intraoperative trauma and intensive bleeding ( 36 ).…”
Section: Vascular Ehlers-danlos Syndromementioning
confidence: 99%
“…With various reported developments of intraoperative complications such as choroidal detachment, hemorrhage, and subsequent scarring, success of surgical repair for rhegmatogenous retinal detachments in patients with vEDS is especially low ( 35 ). In one case of a patient with type IV EDS presenting with retinal detachment accompanied by vitreous hemorrhage and ten retinal breaks, Lumi et al reported successful repair utilizing a small-gauge vitrectomy with gas tamponade and laser photocoagulation to avoid intraoperative trauma and intensive bleeding ( 36 ).…”
Section: Vascular Ehlers-danlos Syndromementioning
confidence: 99%